Essential Oil Content and Concentration of Constituents of Lemon Balm (Melissa officinalis L.) at Different Harvest Dates. Issue 5 (3rd September 2018) - Said-Al Ahl, Hussein A.H.; Sabra, Ali S.; Gendy, Ahmed S.H.; Astatkie, Tess
Abstract: Lemon balm ( Melissa officinalis L.) is a perennial herb that is widely used in traditional medicines. An experiment was conducted under the agro-climatic conditions of National Research Centre, Giza, Egypt to determine the effect of time of harvesting on essential oil content and quality of M. officinalis . Essential oil content, and the concentrations of neral and geranial were measured from the fresh aerial parts of the plant during twelve monthly harvesting times, starting from May 2013 and ending in April, 2014. The starting time was two months after transplanting. Results of the statistical analysis revealed ontogenetic variability in the essential oil content of lemon balm. The highest essential oil content was obtained in September harvesting, followed by August and then by October harvesting time. Neral (20.1-35.0%) and geranial (23.8-51.2%) were the major constituents found in the essential oil and they varied with the harvest time. The results of this study suggest that the highest essential oil content of M. officinalis can be obtained by harvesting it in warmer months (September, August and October).